Is the unconscious, if it exists, a superior decision maker?. Issue 1 (24th January 2014) - Huizenga, Hilde M.; van Duijvenvoorde, Anna C. K.; van Ravenzwaaij, Don; Wetzels, Ruud; Jansen, Brenda R. J.
Abstract Newell & Shanks (N&S) show that there is no convincing evidence that processes assumed to be unconscious and superior are indeed unconscious. We take their argument one step further by showing that there is also no convincing evidence that these processes are superior. We review alternative paradigms that may provide more convincing tests of the superiority of (presumed) unconscious processes.